Assessing the Anthelmintic Candidates BLK127 and HBK4 for Their Efficacy on Haemonchus contortus Adults and Eggs, and Their Hepatotoxicity and Biotransformation - Markéta Zajíčková; Lukáš Prchal; Ivan Vokřál; Linh Thuy Nguyen; Thomas Kurz; Robin Gasser; Klára Bednářová; Magdalena Mičundová; Beate Lungerich; Oliver Michel; Lenka Skálová (MDPI AG, 2022)
As a widely distributed parasitic nematode of ruminants, Haemonchus contortus has become resistant to most anthelmintic classes, there has been a major demand for new compounds against H. contortus and related nematodes. Recent phenotypic screening has revealed two compounds, designated as BLK127 and HBK4, that are active against H. contortus larvae. The present study was designed to assess the activity of these compounds against H. contortus eggs and adults, hepatotoxicity in rats and sheep, as well as biotransformation in H. contortus adults and the ovine liver. Both compounds exhibited no inhibitory effect on the hatching of eggs. The benzyloxy amide BLK127 significantly decreased the viability of adults in sensitive and resistant strains of H. contortus and showed no hepatotoxic effect, even at the highest concentration tested (100 µM). In contrast, HBK4 had no impact on the viability of H. contortus adults and exhibited significant hepatotoxicity. Based on these findings, HBK4 was excluded from further studies, while BLK127 seems to be a potential candidate for a new anthelmintic. Consequently, biotransformation of BLK127 was tested in H. contortus adults and the ovine liver. In H. contortus, several metabolites formed via hydroxylation, hydrolysis and glycosidation were identified, but the extent of biotransformation was low, and the total quantity of the metabolites formed did not differ significantly between the sensitive and resistant strains. In contrast, ovine liver cells metabolized BLK127 more extensively with a glycine conjugate of 4-(pentyloxy)benzoic acid as the main BLK127 metabolite.